Pooling management and transport optimization of packing boxes for motor engine parts. (May 2019) - Wang, Bin; Su, Zhanhao; Wang, Ao; Chen, Kang
Based on the analysis of current inbound logistics and packing box utilization of a motor engine factory and the demand for the parts from motor engine factories, we propose a new logistics system by establishing a packing box pooling center and using milk-run picking to load the empty and full packing boxes. A programming model for locating pooling centers and transporting the packing boxes is established with the objective of minimizing the total transport cost for the parts logistics. A solution algorithm is designed and used for sensitivity analyses of the effects of changing pooling centers on the inbound logistics cost.